Implementasi Algoritma K-Means Clustering terhadap Tingkat Kepuasan Peserta LKP Multi Talenta Komputer Purwokerto - Faozan Dwiki Ramadana; Wahyu Putra Pratama; Cannes Lingga Yogario; Abdul Khohar; Ito Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to measure the level of participant satisfaction with learning services at LKP Multi Talenta Komputer Purwokerto. Participant satisfaction is an important indicator in assessing the effectiveness of the learning curriculum implemented. Factors such as facilities, services, and obstacles in learning become the main benchmark. Data from 54 respondents were processed using K-Means Clustering algorithm to identify the most superior and weak factors. The results of this study provide recommendations for future service improvements, in order to increase participant loyalty and learning effectiveness.